Slow cryopreservation is not superior to vitrification in human spermatozoa; an experimental controlled study - Mohamed Shehata Ali Mohamed (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Spermatozoa cryopreservation is used for the management of infertility and some other medical conditions. The routinely applied cryopreservation technique depends on permeating cryoprotectants, whose toxic effects have raised the attention towards permeating cryoprotectants-free vitrification technique. Objective: To compare between the application of slow cryopreservation and vitrification on human spermatozoa. Materials and Methods: This was an experimental controlled study involving 33 human semen samples, where each sample was divided into three equal parts; fresh control, conventional slow freezing, and permeating cryoprotectants-free vitrification. Viability and mitochondrial membrane potential (MMP) of control and post-thawing spermatozoa were assessed with the sperm viability kit and the JC-1 kit, respectively, using fluorescence-activated cell sorting analysis. Results: Significant reduction of the progressive motility, viability and MMP was observed by the procedure of freezing and thawing, while there was not any significant difference between both cryopreservation techniques. Cryopreservation resulted in 48% reduction of the percentage of viable spermatozoa and 54.5% rise in the percentage of dead spermatozoa. In addition, high MMP was reduced by 24% and low MMP was increased by 34.75% in response to freezing and thawing. Progressive motility of spermatozoa was correlated significantly positive with high MMP and significantly negative with low MMP in control as well as post-thawing specimens (r=0.8881/ -0.8412, 0.7461/ -0.7510 and 0.7603/ -0.7839 for control, slow and vitrification respectively, p=0.0001). Conclusion: Although both cryopreservation techniques have similar results, vitrification is faster, easier and associated with less toxicity and costs. Thus, vitrification is recommended for the clinical application.